Single-centre analysis of common intracranial pathologies among emergency patients using head CT / Nur Syamimi Nazri and Zanariah Mohd - Nazri, Nur Syamimi; Mohd, Zanariah (Faculty of Health Sciences, Universiti Teknologi MARA, 2024)
Head Computed Tomography (CT) is an essential diagnostic imaging tool for detecting intracranial pathologies. Given the association of CT scans with ionizing radiation, it is crucial to implement appropriate safety measures. CT scan requests should be well justified to avoid unnecessary procedures that could lead to adverse patient effects. This study evaluates the prevalence of common intracranial pathologies and assesses the relationship between clinical indications and CT findings among emergency department patients. A total of 177 radiological CT reports from the emergency department between October and December 2022 were reviewed. Variables including age, gender, clinical indications, and radiological findings were recorded. Statistical analysis was performed using SPSS, with the chi-square test used to assess relationships (α<0.05). Out of the 177 CT reports, 61% were male, and 39% were female, with a mean age of 61 ± 20 years. Normal findings were reported in 55.4% of the studies. The most common abnormal finding was ischemic infarcts, present in 15.3% of reports. There was no statistically significant relationship between CT findings and clinical indications. Most CT studies requested in the emergency department revealed normal findings. Understanding the prevalence of common intracranial findings and their clinical correlations can improve patient management strategies.